Behaviors, Experiences, and Needs of Senior Tourists Visiting Khao Yai National Park - Pingkaew, Natthineeporn; Jittithavorn, Chomponuch; Na Talang, Chawalee; Pongponrat, Kannapa (Dusit Thani College Journal, 2020)
This study aimed to investigate behaviors, experiences, and needs of senior tourists visiting to Khao Yai National Park. This qualitative research employed in-depth interview method of data collection with 40 senior tourists visiting to Khao Yai National Park in 2019. The results indicated that firstly, in the aspect of behaviors, senior tourists visiting to Khao Yai National Park mostly traveled in groups which were divided into three types, including family group (husband and wife), family group (children and grandchildren), and friends. In addition, the purposes of traveling were relaxation, nature, fresh air, camping, and Chao Pho Khao Yai Shrine. For information, senior tourists accessed to information by themselves from online media and information from acquaintances. They used private cars as their vehicle; besides, popular leisure activities among the senior tourists were traveling along natural attractions, exercise, camping, and gaining knowledge in tourist service center. In aspect of the expense of traveling, it varied among senior tourists, depending on the number of the days spending on each trip. Secondly, in the aspect of experiences, most senior tourists gained experiences from entirely three aspects which were people, places, and activities. Thirdly, the needs of the senior tourists visiting to Khao Yai National Park, the senior tourists indicated accommodation quality, the physical environment of attractions, and services and hospitality of officers should be improved and developed. Furthermore, the tourist management of Khao Yai National Park was needed to improve the efficiency and convenience for the senior tourists. In addition, in the aspect of advertising and public relation, senior tourists required more modern public relation channels to encourage the tourists to increasingly travel to Khao Yai National Park.